Analisis Ketersediaan Fasilitas dan Pembiayaan Kesehatan pada Pelaksanaan Jaminan Kesehatan Nasional di Provinsi Bengkulu - Yandrizal Yandrizal; Hendarin Hendarin; Desri Suryani (Jurnal Kebijakan Kesehatan Indonesia, 2014)
The Background: National health assurance program aims to facilitate community access to quality health services. Health financing toward Universal Coverage is a good breakthrough but it can cause negative effects in the form of injustice. Availability of health facilities, health care personel and geographical condition and the broad population dispersion can magnify the problem of inequities between subdistricts and district/city in Bengkulu province, making it appear unequal in health services and financing. Availability of health facilities with inappropriate amount of power impacting the financing needs of the social security in health facilities in the form of capitation and INA-CBG package, and equitable financing analysis needs to be done in the implementation of the national health assurance policy. The purpose: Assesing the availability of facilities and even distribution of financing health and also to equalize of health facilities and drawing up scenarios of possibility of the future in the implementation of the national health insurance in the Province of Bengkulu. Method: This research uses the formative analysis methods designed to assess how the program/policy is being implemented and how it is thought to modify and develop to bring an improvement. Results: The ratio of first-level health facilities (FKTP), which is likely a general practitioner, according to the road map leading to JKN 2012-2019 should achieve the ratio of general practitioners 1: 3000 inhabitants.Currently the average in Bengkulu is 1 per 7.715 inhabitants, thus the need for first- level health facilities in the province of Bengkulu is 590 units. Beginning in 2014, 229 is available until the year 2019, and is still lacking as much as 361 units. Clinics with magnitudes capitation of Rp. 3,000 up to Rp. 4500 is 51.57% and while capitation of Rp. 6,000 is 13.3%. Capitation quantity is uneven financing that have an impact especially on the health of urban areas due to lack of resources. The value of the contract for one year for the number of participants who choose Clinics as FKTP is 763.165 people which is 82,03% of the maximum value of capitation Rp. 6,000, or less Rp9,87M. The average rate on the 7 (seven) Regional public hospitals district and Province for outpatient is between Rp. 150.000 s. d Rp. 350,000 and hospitalization is Rp. 1.000.000,-until Rp. s. 3.700.000,-, compared to the rates based on regulation of the Minister of health RI Number 69 by 2013, the average price of outpatient service and inpatient medical action is very simple and only for mild categories of diseases. Shortage of specialist doctors in Hospital causes unabsorbed INA-CBG package for major treatment action and severe categories of disease. Financial support the Government district/city and Province in the form of program jamkesda 2014 is IDR 38,36 M to pay for the capitation for the poor who are not covered by central government funding and to ensure treatment for kabupaten/ kota that did not cooperate with the BPJS. Incentive specialist doctor/resident is between IDR10 million to 30 million per month, especially the big four specialists from the local government district is another inequalities that is burdensome to the local government; The fulfillment of resources especially General practitioners and dentists in clinics is difficult to materialize given that CPNS (civil servant) formation are very small; the County Government could offer contracts but they can not afford it and it is not worth the lack of capitation. While the fulfillment specialist doctors in Hospitals is also difficult because there is lack of enthusiasm to become specialist CPNS , and the Country Government could not affort contract for them. Fulfillment needs efforts in health facilities first-level, general practitioners, dentists and specialists required a revision of the regulation of the Minister of health no. 69 year 2013 by observing the rate of capitation and INA-CBG¡¯s package for underserved areas away from urban center, or with small population and vast distribution of people. Conclusion: First-level health facilities and the number of personnel in clinics and specialist doctors in the hospital are still lacking, impacting the small capitation and the claim is limited to a minor treatment and mild disease. Regulation of the Minister of health RI Number 69 by 2013 on Standard Rate of health services need to pay attention to differences in geographical situation where Clinics and public hospitals are in the region. Latar Belakang: Program Jaminan Kesehatan Nasional bertujuan mempermudah masyarakat untuk mengakses pelayanan kesehatan yang bermutu. Pembiayaan kesehatan menuju Universal Coverage merupakan terobosan yang baik tetapi dapat menimbulkan dampak negatif berupa ketidakadilan. Ketidamerataan ketersediaan fasilitas kesehatan, tenaga kesehatan dan kondisi geografis serta penyebaran penduduk yang luas dapat memperbesar masalah ketidakadilan antar kecamatan dan kabupaten/kota di Provinsi Bengkulu, sehingga muncul ketidakmerataan pelayanan dan pembiayaan kesehatan. Ketersedian fasilitas kesehatan dengan jumlah tenaga yang tidak sesuai kebutuhan berdampak pada pembiayaan dari Badan Penyelenggara Jaminan Sosial Kesehatan dalam bentuk kapitasi dan Paket INA-CBG¡¯s, maka perlu dilakukan analisis pemerataan pembiayaan pada kebijakan pelaksanaan jaminan kesehatan nasional. Tujuan: Mengetahui ketersediaan fasilitas dan pemerataan pembiayaan kesehatan serta upaya pemerataan fasilitas kesehatan dan menyusun skenario kemungkinan masa mendatang dalam pelaksanaan jaminan kesehatan nasional di Provinsi Bengkulu. Metode: Penelitian ini menggunakan rancangan metode analisis formatif yang dirancang untuk menilai bagaimana program/kebijakan sedang diimplementasikan dan bagaimana pemikiran untuk memodifikasi serta mengembangkan sehingga membawa perbaikan. Hasil: Rasio fasilitas kesehatan tingkat pertama (FKTP) yang disamakan satu dokter umum, Peta Jalan Menuju JKN 2012- 2019 rasio dokter umum 1 : 3000 penduduk, maka rata-rata 1 per 7.715 penduduk, kebutuhan fasilitas kesehatan tingkat pertama di Provinsi Bengkulu sebanyak 590 unit. Awal tahun 2014 yang tersedia 229 sampai tahun 2019 masih kurang sebanyak 361 unit. Puskesmas dengan besaran kapitasi Rp3000,00 s.d Rp4.500,00 sebanyak 51,57% dan Rp6.000,00 sebanyak 13,3%. Besaran kapitasi berdampak tidak merata pembiayaan terutama di Puskesmas yang jauh dari perkotaan karena kekurangan tenaga. Nilai kontrak selama satu tahun jumlah peserta yang memilih Puskesmas sebagai FKTP sebanyak 763.165 jiwa sebesar 82,03% dari nilai maksimal kapitasi Rp6.000,00 atau kurang 9,87M. Tarif rerata pada tujuh Rumah Sakit Umum Daerah Kabupaten dan Provinsi untuk rawat jalan antara Rp. 150.000 s.d Rp640.000,00 dan rawat inap Rp1.000.000,00 s.d Rp3.700.000,00 dibandingkan tarif berdasarkan Peraturan Menteri Kesehatan RI Nomor 69 Tahun 2013, rata-rata tarif pelayanan rawat jalan dan rawat inap merupakan tarif tindakan medis sangat sederhana dan penyakit- penyakit katagori ringan. Kekurangan dokter spesialis di RSUD menyebabkan tidak terserap paket INA-CB¡¯s untuk tindakan besar dan penyakit katagori berat. Dukungan dana Pemerintah Kabupaten/Kota dan Provinsi dalam bentuk program jamkesda tahun 2014 sebesar 38,36 M untuk membayar kapitasi masyarakat miskin bukan penerima bantuan iuran dan menjamin pengobatan bagi kabupaten/kota yang tidak bekerja sama dengan BPJS. Insentif dokter spesialis/residen antara 10 juta s.d 30 juta per bulan terutama spesialis empat besar dari pemerintah daerah kabupaten merupakan ketidakadilan pembiayaan yang menjadi beban daerah. Pemenuhan tenaga terutama dokter umum, dokter gigi di puskesmas sulit terwujud mengingat formasi CPNS sangat kecil, apabila dilakukan kontrak Pemerintah Kabupaten tidak mampu dan tidak sebanding dengan kekurangan kapitasi. Sedangkan pemenuhan dokter spesialis di RSUD juga sulit terwujud karena peminat CPNS untuk dokter spesialis tidak ada dan apabila dilakukan kontrak sebesar insentif Pemerintah Kabupaten tidak mampu. Upaya pemenuhan kebutuhan fasilitas kesehatan tingkat pertama, dokter umum, dokter gigi dan spesialis diperlukan revisi Peraturan Menteri Kesehatan No.69 tahun 2013 tentang tarif dengan memperhatikan kapitasi dan paket INA-CBG¡¯s di daerah tidak diminati atau jauh dari perkotaan, jumlah penduduk kecil serta sebaran yang luas. Kesimpulan. Fasilitas kesehatan tingkat pertama dan jumlah tenaga di puskesmas dan dokter spesialis di rumah sakit masih kurang, berdampak kecilnya kapitasi dan klaim terbatas pada tindakan kecil serta penyakit yang ringan. Peraturan Menteri Kesehatan RI Nomor 69 Tahun 2013 Tentang Standar Tarif Pelayanan Kesehatan perlu memperhatikan geografis dimana Puskesmas dan Rumah Sakit Umum Daerah.